1993
DOI: 10.1128/mcb.13.3.1610
|View full text |Cite
|
Sign up to set email alerts
|

A protein synthesis-dependent increase in E2F1 mRNA correlates with growth regulation of the dihydrofolate reductase promoter.

Abstract: Enhanced expression of genes involved in nucleotide biosynthesis, such as dihydrofolate reductase (DHFR), is a hallmark of entrance into the DNA synthesis (S) phase of the mammalian cell cycle. To investigate the regulated expression of the DHFR gene, we stimulated serum-starved NIH 3T3 cells to synchronously reenter the cell cycle. Our previous results show that a cis-acting element at the site of DHFR transcription initiation is necessary for serum regulation. Recently, this element has been demonstrated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
254
1
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(270 citation statements)
references
References 49 publications
14
254
1
1
Order By: Relevance
“…22 Subsequent studies have shown that E2F controls the transcription of cellular genes that are essential for cell division, such as enzymes involved in the biosynthesis of nucleotides. 23 In the 1990s, Nevins et al 24 deduced how E2F is regulated in normal cells by determining the mechanism of E2F activation by E1A. E1A caused a cellular protein to dissociate from E2F, which led them to show that E2F is inhibited by its association with Rb.…”
Section: A Role In Cancermentioning
confidence: 99%
“…22 Subsequent studies have shown that E2F controls the transcription of cellular genes that are essential for cell division, such as enzymes involved in the biosynthesis of nucleotides. 23 In the 1990s, Nevins et al 24 deduced how E2F is regulated in normal cells by determining the mechanism of E2F activation by E1A. E1A caused a cellular protein to dissociate from E2F, which led them to show that E2F is inhibited by its association with Rb.…”
Section: A Role In Cancermentioning
confidence: 99%
“…To investigate further the mechanism by which PARP contributes to regulation of pol a gene transcription during early S phase, we examined the e ect of PARP depletion by gene knockout on the abundance of E2F-1, a transcription factor that positively regulates the transcription of several genes whose products are required for DNA replication and cell growth; these genes include those encoding pol a, PCNA, dihydrofolate reductase, thymidine kinase, c-MYC, c-MYB, cyclin D, cyclin E, and E2F-1 itself (Blake and Azizkhan, 1989;DeGregori et al, 1995;Nevins, 1992;Pearson et al, 1991;Slansky et al, 1993). We previously demonstrated that PARP depletion by antisense RNA expression in 3T3-L1 cells prevents induction of E2F-1 expression during the early stages of di erentiation-linked DNA replication (SimbulanRosenthal et al, 1998a).…”
Section: Parp7/7 Cells Do Not Show the Marked Induction Of E2f-1 Exprmentioning
confidence: 99%
“…The transcriptional activity of members of the E2F family of transcription factors is regulated by multiple cell cycle-related events, such as increased expression (transcriptionally or post-transcriptionally) (Slansky et al, 1993), phosphorylation (for E2F-1, 2 and 3) by cyclin A/cdk2 complexes (Xu et al, 1994) and complex formation with pRb or pRb-related proteins p107 and p130. Therefore, increased expression of the E2F protein may not necessarily lead to increased transcriptional activity.…”
Section: Induction Of the E2f Transcription Factors By Activated K-ramentioning
confidence: 99%